2013
DOI: 10.1167/iovs.13-12500
|View full text |Cite
|
Sign up to set email alerts
|

TLR-Independent and P2X7-Dependent Signaling MediateAluRNA-Induced NLRP3 Inflammasome Activation in Geographic Atrophy

Abstract: NF-κB and P2X7 are critical signaling intermediates in Alu RNA-induced inflammasome priming and RPE degeneration. These molecules are novel targets for rational drug development for geographic atrophy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
134
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(140 citation statements)
references
References 28 publications
5
134
1
Order By: Relevance
“…Amyloid β, perhaps best known for its suspected role in Alzheimer's disease (Kang et al 1987;Hardy and Higgins 1992;Hardy and Selkoe 2002), was found to be a drusen component in AMD patients (Johnson et al 2002;Dentchev et al 2003). Ocular amyloid deposits in a mouse model of Alzheimer's disease were associated with retinal degeneration (Ning et al 2008) and RPE stress , and amyloid β is known to activate the NLRP3 inflammasome (Halle et al 2008), consistent with other findings that inflammasome activation may mediate GA Kerur et al 2013;Kim et al 2014;Gelfand et al 2015). Based on the studies suggesting amyloid β accumulation may contribute to ocular pathologies in mouse models of AMD Catchpole et al 2013), a clinical trial testing the efficacy of a monoclonal antibody against amyloid β is currently underway (Danis et al 2015).…”
Section: Neuroprotective Agentssupporting
confidence: 79%
See 1 more Smart Citation
“…Amyloid β, perhaps best known for its suspected role in Alzheimer's disease (Kang et al 1987;Hardy and Higgins 1992;Hardy and Selkoe 2002), was found to be a drusen component in AMD patients (Johnson et al 2002;Dentchev et al 2003). Ocular amyloid deposits in a mouse model of Alzheimer's disease were associated with retinal degeneration (Ning et al 2008) and RPE stress , and amyloid β is known to activate the NLRP3 inflammasome (Halle et al 2008), consistent with other findings that inflammasome activation may mediate GA Kerur et al 2013;Kim et al 2014;Gelfand et al 2015). Based on the studies suggesting amyloid β accumulation may contribute to ocular pathologies in mouse models of AMD Catchpole et al 2013), a clinical trial testing the efficacy of a monoclonal antibody against amyloid β is currently underway (Danis et al 2015).…”
Section: Neuroprotective Agentssupporting
confidence: 79%
“…A series of studies published within the last five years indicate DICER1 reduction in GA patients may contribute to RPE cell death because the enzyme is required to degrade cytotoxic Alu RNA transcripts (Kaneko et al 2011). Increases in Alu RNA transcripts in GA patients cause activation of the NLRP3 inflammasome Dridi et al 2012), ultimately resulting in P2X7-dependent Caspase-8-mediated RPE cell death (Kerur et al 2013;Kim et al 2014). These observations are supported by other data showing this signaling pathway can be instigated by the presence of excess iron (Gelfand et al 2015), which has also been previously associated with AMD in humans (Wong et al 2007).…”
Section: Inflammatory Modulatorsmentioning
confidence: 99%
“…72 For example, cells from eyes with AMD exhibit upregulated expression of immune receptors and molecules, 73,74 including expression of IL-17RC, a receptor for a dimer of IL-17A and IL-17F and activation of NLRP3 inflammasome, that promotes cleavage of pro-IL-1beta and IL-18. [75][76][77] Furthermore, both macrophages and multinucleated giant cells, mainly associated with vascular channels and breaks in Bruch's membrane are evident. [78][79][80][81][82][83] Macrophage subtype changes have been noted in the eyes of patients with AMD, including a change in the M1/M2 ratio in AMD eyes, compared with that in control eyes of the same age.…”
Section: Understanding Uveitismentioning
confidence: 99%
“…For instance, in human cells, endogenous dsRNA formed by pairing of inverted Alu repeats is released from the nucleus during mitosis to activate the dsRNA-binding protein PKR, and repress translation (Kim et al 2014). In a potentially related example, elevated levels of endogenous, repetitive Alu RNA, resulting from Dicer deficiency, leads to noncanonical activation of the NLRP3 inflammasome via MyD88 signaling (Tarallo et al 2012;Kerur et al 2013). Structured elements within mRNAs also serve as important regulatory elements, influencing translatability and stability.…”
Section: Introductionmentioning
confidence: 99%